Persistent Pyrexia in Tetanus: A Case Report from Nepal - Khadka, Bikash; Khanal, Kishor; Sharma, Nisha (Birat Journal of Health Sciences, 2022)
Tetanus, an infection caused by the gram-positive, obligate anaerobic bacillus Clostridium tetani, is still prevalent in developing countries. Fever is an unusual symptom in tetanus. The disease must be managed by preventing tetanospasmin absorption, treating symptoms, stabilizing autonomic instability, using antibiotics, and controlling the airway with assisted ventilation if necessary. We present a case report of a tetanus patient who had persistent pyrexia despite ruling out all the obvious causes of fever ,that coincide with the persistence of muscle spasms and/or use of prolonged duration of benzodiazepines.